The trade-wage debate in a model with nontraded goods: making room for labor economists in labor theory - Robinson, Sherman; Thierfelder, Karen (International Food Policy Research Institute, 1996)
The Heckscher-Ohlin-Samuelson (HOS) model in international trade theory provides a powerful general-equilibrium paradigm for analyzing the impact of changes in trade on factor returns. In the HOS model, factor returns are determined solely by commodity prices, which are determined on large world markets. Changes in factor supplies affect the structure of production and trade, but not relative factor returns. In this framework, there is little room for labor economists who focus on partial-equilibrium analysis of supply and demand in factor markets. The authors extend the HOS model to include nontraded goods, distinguishing them theoretically from "nontradable" goods. The resulting 1-2-2-3 model applied to one country with two production activities using two factors of production but consuming a third imported good. We show that the HOS model is a special case of the 1-2-2-3 model when imports and domestic goods are perfect substitutes."